ANALISIS PENERAPAN ACTIVITY BASED COSTING DALAM PENENTUAN HARGA POKOK PRODUKSI - Ashari Normala Putri; have zulkarnaen (Pro-fit, 2023)
The Activity Based Costing (ABC) system can provide better costing information and can help management manage the company efficiently and gain a better understanding of the company's strengths, weaknesses and competitive advantages. So that the ABC method can present the cost of production information carefully and accurately for the benefit of management. The purpose of this study was to determine the cost of production at CV. Ulung Gunungsari Baureno Bojonegoro and to determine the effectiveness of HPP using the ABC method when compared to traditional calculations. The analytical method used is descriptive quantitative. The results showed that the HPP calculation using ABC gave higher results than the traditional method on CV.Ulung. the traditional system provides a lower HPP price calculation because the calculation with the traditional system only uses one cost driver so that there is a lot of cost distortion and results in irrelevant HPP calculations. The company should re-evaluate the costing system in determining the HPP.